Abuse of Pesticides and Environmental Impacts in Vietnam - Chung, Kieu Thi Thu (International Journal of Psychosocial Rehabilitation, 2020)
Pesticides have the main purpose of preventing insect pests. Therefore, the abuse of pesticides to preserve food seriously affects human health. The elimination of highly toxic pesticides in agricultural production will contribute to ensuring the quality of agricultural products as well as the health of users. However, in some places in Vietnam, businesses still surreptitiously produce fake pesticides, which are on the banned list for sale in the market, especially in remote areas. Vietnam is one of the countries using to much pesticides and it is difficult to control. This abuse will be harmful to producers, communities and environment, this also reduces product competition and causes land degradation. Meanwhile, the effectiveness from encouraging research, production, trading and application of biological measures and biological pesticides to fight harmful organisms in Vietnam is not high. The paper focuses on the current status of pesticide use in Vietnam. This abuse will have great consequences and we need appropriate solutions to create a healthier and cleaner living environment.